Anaesthetic Management of a Morbidly Obese Parturient for Elective Caesarean Section - Pradhan, R; Shrestha, S; Gurung, T; Shrestha, AB; Sharma, KR (Nepal Journal of Obstetrics and Gynaecology, 2016)
Anaesthesia for an obese parturient poses a challenge to anaesthesiologists. Here we report a case of 27 years obese primigravidae at 40 weeks of gestation with gestational hypertension who underwent elective cesarean section under combined spinal epidural anaesthesia. Her intraoperative and postoperative periods were uneventful.